'Conservative nativist' Chinese art in Hong Kong and Mainland China. (1st March 2014) - Vigneron, Frank
In the discourse on 'nativism' and 'cultural conservatism', now dominant in Mainland China, the position of 'traditional' art, and especially painting made with Chinese ink, has been promoted by official institutions like the China Artists Association, thus emphasizing the support of the state. The discourse accompanying the appreciation and creation of Ink art in Mainland China has thus been stated with an often extremely nationalistic attitude. When Ink art belongs to art practices seen as 'contemporary' and therefore not 'traditional' in Mainland China, it is generally ignored by official, state-sponsored institutions. Both 'traditional' and 'contemporary' Ink art practices also coexist in Hong Kong, but even the traditional is generally defended without recourse to the kind of excessive cultural nationalism prevalent in the Mainland (even though there is always the possibility for Hong Kong nativist conservatives to exhibit in China, where they can rely on the official promotion of their art). Hong Kong public and private art institutions have also defended Ink art, thus redefining its function and boundaries. The role of M+ and the museums of the Leisure and Cultural Services Department have been instrumental in the promotion and expansion of the field of Ink art.